I have homework to evaluate this integral $$I=\int_{0}^{\infty} \frac{\tanh(x)\,\tanh(2x)}{x^2}\;dx$$

Here is what I have done so far. I tried integration by parts using $u=\tanh(x)\,\tanh(2x)$ and $dv=\frac{dx}{x^2}$, I got $$\begin{align}\int_{0}^{\infty} \frac{\tanh(x)\,\tanh(2x)}{x^2}\;dx&=-\left.\frac{\tanh(x)\,\tanh(2x)}{x}\right|_{0}^{\infty}+2\int_{0}^{\infty}\frac{\tanh(2x)\,\text{sech}(2x)}{x}\;dx\\&=2\int_{0}^{\infty}\frac{\tanh(2x)\,\text{sech}(2x)}{x}\;dx\end{align}$$ At this part I'm stuck. I'm thinking of using Frullani's integral but I'm having trouble to find a relation as such $\tanh(2x)\,\text{sech}(2x)=f(ax)-f(bx)$.

I also tried using differentiation under integral sign by considering $$I(a,b)=\int_{0}^{\infty} \frac{\tanh(ax)\,\tanh(bx)}{x^2}\;dx$$ then $$\frac{dI}{da}=\int_{0}^{\infty} \frac{\text{sech}^2(ax)\,\tanh(bx)}{x}\;dx=\int_{0}^{\infty} \frac{\tanh(bx)-\tanh^2(ax)\tanh(bx)}{x}\;dx$$ Again I tried to use Frullani's integral but I'm having trouble to find the sufficient $f(x)$. Integrating again with respect to $b$, I got $$\frac{d^2I}{da\;db}=\int_{0}^{\infty} \text{sech}^2(ax)\text{sech}^2(bx)\;dx$$ It's obviously a dead end to me. At this rate my friends and I contacted my professor to confirm whether the integral can be evaluated in terms of elementary functions or not because W|A cannot find it (I know that W|A cannot do everything). He only said, "Sure! The answer is only 3 characters" and then he left us. Assuming he is right, so $I$ must have a nice closed form, but I'm unable to find it.

Would you help me? Any help would be appreciated. Thanks in advance.

  • $\begingroup$ just as comment: The substitution $x=arctanh(y)$ together with $\tanh(2x)=\frac{2 \tanh(x)}{1+\tanh(x)^2}$ is maybe worth to give it a try. $\endgroup$ – tired Nov 11 '14 at 17:47
  • $\begingroup$ @tired I did, but it got complicated $\endgroup$ – Venus Nov 11 '14 at 17:51
  • $\begingroup$ at which point? $\endgroup$ – tired Nov 11 '14 at 17:54
  • $\begingroup$ @tired At the denominator: $\text{arctanh}\,(y)^2$ $\endgroup$ – Venus Nov 11 '14 at 17:55
  • $\begingroup$ i tried a litte bit, and indeed things didn't get really easier...:-( $\endgroup$ – tired Nov 11 '14 at 19:04

Your professor is right. Note that $$ \tanh(x)=\frac{e^x-e^{-x}}{e^x+e^{-x}}, \tanh(2x)=\frac{e^{2x}-e^{-2x}}{e^{2x}+e^{-2x}}=\frac{(e^x-e^{-x})(e^x+e^{-x})}{e^{2x}+e^{-2x}}$$ and hence \begin{eqnarray*} \int_0^\infty\frac{\tanh(x)\tanh(2x)}{x^2}dx&=&\int_0^\infty\frac{(e^{x}-e^{-x})^2}{x^2(e^{2x}+e^{-2x})}dx\\ &=&\int_0^\infty\frac{e^{2x}-2+e^{-2x}}{x^2(e^{2x}+e^{-2x})}dx. \end{eqnarray*} Now define $$ I(a)=\int_0^\infty\frac{e^{ax}-2+e^{-ax}}{x^2(e^{2x}+e^{-2x})}dx$$ to get \begin{eqnarray} I''(a)&=&\int_0^\infty\frac{e^{(-a-2)x}+e^{(-a+2)x}}{1+e^{-4x}}dx,\\ &=&\int_0^\infty\sum_{n=0}^\infty(-1)^n(e^{(-a-2)x}+e^{(-a+2)x})e^{-4nx}dx\\ &=&\sum_{n=0}^\infty(-1)^n\left(\frac{1}{4n-a+2}+\frac{1}{4n+a+2}\right)\\ &=&\frac{\pi}{4}\sec\left(\frac{a\pi}{4}\right). \end{eqnarray} So \begin{eqnarray} I'(a)&=&\int_0^a\frac{\pi}{4}\sec\left(\frac{\pi t}{4}\right)dt\\ &=&\ln\left(1+\sin\left(\frac{\pi a}{4}\right)\right)-\ln\cos\left(\frac{\pi a}{4}\right) \end{eqnarray} and hence \begin{eqnarray} I(2)&=&\int_0^2\ln\left(1+\sin\left(\frac{\pi a}{4}\right)\right)da-\int_0^2\ln\cos\left(\frac{\pi a}{4}\right)da. \end{eqnarray} Note $$ \int_0^2\ln\cos\left(\frac{\pi a}{4}\right)da=-2\ln2 $$ from Evaluating $\int_0^{\large\frac{\pi}{4}} \log\left( \cos x\right) \, \mathrm{d}x $ and it should not be hard to get $$ \int_0^2\ln\left(1+\sin\left(\frac{\pi a}{4}\right)\right)da=\frac{8G}{\pi}-2\ln 2$$ and thus $$ I(2)=\frac{8G}{\pi}. $$

$\bf{Update}$ 1: Let us first work on $ \sum_{n=0}^\infty(-1)^n\left(\frac{1}{4n-a+2}+\frac{1}{4n+a+2}\right)=\frac{\pi}{4}\sec\left(\frac{a\pi}{4}\right)$. In fact \begin{eqnarray*} &&\sum_{n=0}^\infty(-1)^n\left(\frac{1}{4n-a+2}+\frac{1}{4n+a+2}\right)\\ &=&\sum_{n=0}^\infty\left(\frac{1}{8n-a+2}-\frac{1}{8n-a+6}\right)+\sum_{n=0}^\infty\left(\frac{1}{8n+a+2}-\frac{1}{8n+a+6}\right)\\ &=&\sum_{n=0}^\infty\frac{4}{(8n-a+2)(8n-a+6)}+\sum_{n=0}^\infty\frac{4}{(8n+a+2)(8n+a+6)}\\ &=&\sum_{n=-\infty}^\infty\frac{4}{(8n-a+2)(8n-a+6)}=\sum_{n=-\infty}^\infty\frac{4}{(8n-a+4)^2-2^2}\\ &=&\frac{1}{16}\sum_{n=-\infty}^\infty\frac{1}{(n+\frac{4-a}{8})^2-(\frac{1}{4})^2}. \end{eqnarray*} Now using a result from Closed form for $\sum_{n=-\infty}^\infty \frac{1}{(z+n)^2+a^2}$ for $a=\frac{i}{4}$ and $z=\frac{4-a}{8}$ and after some basic calculation we can get this result. Also see An alternative proof for sum of alternating series evaluates to $\frac{\pi}{4}\sec\left(\frac{a\pi}{4}\right)$ for a short proof.

$\bf{Update}$ 2: We work on $\int_0^2\ln\left(1+\sin\left(\frac{\pi a}{4}\right)\right)da=\frac{8G}{\pi}-2\ln 2$. In fact \begin{eqnarray} \int_0^2\ln\left(1+\sin\left(\frac{\pi a}{4}\right)\right)da=\frac{4}{\pi}\int_0^{\pi/2}\ln\left(1+\sin(a)\right)da=\frac{4}{\pi}\int_0^{\pi/2}\ln(1+\cos(a))da. \end{eqnarray} Using $2\cos^2\frac{a}{2}=1+\cos a$ and a result $G=\int_0^{\pi/4}\ln(\cos(t))dt$ from http://en.wikipedia.org/wiki/Catalan%27s_constant, it is easy to obtain $$ \int_0^2\ln\left(1+\sin\left(\frac{\pi a}{4}\right)\right)da= \frac{8G}{\pi}-2\ln 2. $$

  • $\begingroup$ Amazing! This very simple! You've posted since 19 hrs ago but why I didn't notice it earlier? +1 $\endgroup$ – Venus Nov 12 '14 at 18:19
  • $\begingroup$ Anyway, could you elaborate this part $$\int_0^2\ln\left(1+\sin\left(\frac{\pi a}{4}\right)\right)da=\frac{8G}{\pi}-2\ln 2$$Thanks... $\endgroup$ – Venus Nov 12 '14 at 18:40
  • $\begingroup$ Never mind, I can handle it. Thanks for your simple & nice solution. :-) $\endgroup$ – Venus Nov 12 '14 at 18:43
  • $\begingroup$ Sorry, last question. How I can proof this series $$\sum_{n=0}^\infty(-1)^n\left(\frac{1}{4n-a+2}+\frac{1}{4n+a+2}\right)=\frac{ \pi }{4}\sec\left(\frac{a \pi }{4}\right)$$ Do you have any references? Or did you use residue method? Can you elaborate using real analysis method? Thanks... $\endgroup$ – Venus Nov 12 '14 at 18:49
  • 1
    $\begingroup$ @Venus: Let $u=\dfrac\pi4 a$ and $\sin u=\cos\bigg(\dfrac\pi2-u\bigg)$ and $\dfrac{1+\cos t}2=\cos^2\dfrac t2$ $\endgroup$ – Lucian Nov 12 '14 at 22:54

Here is a method that avoids complex analysis. That being said however, I think achille hui's approach is far superior as this answer uses too much (unnecessarily) heavy machinery.

Let $x\mapsto-\ln{x}$. We get \begin{align} \mathcal{I} =\int^1_0\frac{1-x^2}{1+x^2}\frac{1-x^4}{1+x^4}\frac{{\rm d}x}{x\ln^2{x}} =\int^1_0\left(\frac{1}{x}-\frac{2x}{1+x^4}\right)\frac{{\rm d}x}{\ln^2{x}} \end{align} Define $$\mathcal{I}(\alpha)=\int^1_0\left(\frac{1}{x}-\frac{2x}{1+x^4}\right)\frac{x^{\alpha}{\rm d}x}{\ln^2{x}}$$ Differentiating twice, one obtains \begin{align} \mathcal{I}''(\alpha) =&\frac{1}{\alpha}-2\sum^\infty_{n=0}(-1)^n\int^1_0x^{4n+\alpha+1}{\rm d}x\\ =&\frac{1}{\alpha}-2\sum^\infty_{n=0}\frac{(-1)^n}{4n+\alpha+2}\\ =&\frac{1}{\alpha}-\frac{1}{4}\sum^\infty_{n=0}\frac{1}{n+\frac{\alpha+2}{8}}+\frac{1}{4}\sum^\infty_{n=0}\frac{1}{n+\frac{\alpha+6}{8}}\\ =&\frac{1}{\alpha}+\frac{1}{4}\psi_0\left(\frac{\alpha+2}{8}\right)-\frac{1}{4}\psi_0\left(\frac{\alpha+6}{8}\right) \end{align} Integrate back once. \begin{align} \mathcal{I}'(\alpha) =&\ln{\alpha}+2\ln{\Gamma\left(\frac{\alpha+2}{8}\right)}-2\ln{\Gamma\left(\frac{\alpha+6}{8}\right)}+C_1 \end{align} The constant of integration is, by Striling's asymptotic series, $-3\ln{2}$. Now, recall the fact that $$\int\ln{\Gamma(x)}\ {\rm d}x=\frac{x(1-x)}{2}+\frac{x}{2}\ln(2\pi)+x\ln{\Gamma(x)}-\ln{G(x+1)}+C_2$$ You may find a proof in this answer. Hence, integrating once again, we obtain \begin{align} \mathcal{I}(\alpha) =&\alpha\ln{\alpha}-\alpha-\frac{(\alpha+2)(\alpha-6)}{8}+(\alpha+2)\ln(2\pi)+2(\alpha+2)\ln{\Gamma\left(\frac{\alpha+2}{8}\right)}\\ &-16\ln{G\left(\frac{\alpha+10}{8}\right)}+\frac{(\alpha-2)(\alpha+6)}{8}-(\alpha+6)\ln(2\pi)\\ &-2(\alpha+6)\ln{\Gamma\left(\frac{\alpha+6}{8}\right)}+16\ln{G\left(\frac{\alpha+14}{8}\right)}-3\alpha\ln{2}+C_2\\ =&C_2-4\ln(2\pi)-3\alpha\ln{2}+\alpha\ln{\alpha}+2(\alpha+2)\ln{\Gamma\left(\frac{\alpha+2}{8}\right)}\\ &-2(\alpha+6)\ln{\Gamma\left(\frac{\alpha+6}{8}\right)}-16\ln{G\left(\frac{\alpha+10}{8}\right)}+16\ln{G\left(\frac{\alpha+14}{8}\right)} \end{align} One may use the asymptotic series of the Barnes G (derived from the log-gamma integral and Stirling's) to check that $C_2=4\ln(2\pi)$. Letting $\alpha\to 0$, \begin{align} \mathcal{I} =&\mathcal{I}(0)\\ =&4\ln{\Gamma\left(\frac{1}{4}\right)}-12\ln{\Gamma\left(\frac{3}{4}\right)}-16\ln{G\left(\frac{5}{4}\right)}+16\ln{G\left(\frac{7}{4}\right)} \end{align} It remains to simplify this result. Using the Gamma reflection formula $\Gamma(z)\Gamma(1-z)=\pi\csc(\pi z)$, as well as the Barnes G functional equation $G(z+1)=G(z)\Gamma(z)$, we get $$\mathcal{I}=-6\ln{2}-12\ln{\pi}-16\ln\left(\frac{G\left(\frac{1}{4}\right)}{G\left(\frac{7}{4}\right)}\right)$$ Now recall that $G(z+1)$ has the infinite product representation $$G(z+1)=\left(\sqrt{2\pi}\right)^{z}e^{-\frac{(1+\gamma)z^2+z}{2}}\prod^\infty_{k=1}e^{\frac{z^2}{2k}-z}\left(1+\frac{z}{k}\right)^k$$ Taking the logarithm, \begin{align} \ln{G(z+1)} =&-\frac{z}{2}+\frac{z}{2}\ln(2\pi)-\frac{z^2}{2}-\frac{\gamma z^2}{2}+\sum^\infty_{k=1}\left\{k\ln\left(1+\frac{z}{k}\right)+\frac{z^2}{2k}-z\right\}\\ =&-\frac{z}{2}+\frac{z}{2}\ln(2\pi)-\frac{z^2}{2}-\frac{\gamma z^2}{2}+\sum^\infty_{k=1}\left\{\frac{z^2}{2k}-z+\sum^\infty_{m=1}\frac{(-1)^{m-1}}{m}\frac{z^m}{k^{m-1}}\right\}\\ =&-\frac{z}{2}+\frac{z}{2}\ln(2\pi)-\frac{z^2}{2}-\frac{\gamma z^2}{2}+\sum^\infty_{k=1}\sum^\infty_{m=3}\frac{(-1)^{m-1}}{m}\frac{z^m}{k^{m-1}}\\ =&-\frac{z}{2}+\frac{z}{2}\ln(2\pi)-\frac{z^2}{2}-\frac{\gamma z^2}{2}+\sum^\infty_{m=3}\frac{(-1)^{m-1}\zeta(m-1)}{m}z^m\\ =&-\frac{z}{2}+\frac{z}{2}\ln(2\pi)-\frac{z^2}{2}-\frac{\gamma z^2}{2}+\sum^\infty_{m=2}\frac{(-1)^{m}\zeta(m)}{m+1}z^{m+1}\\ \end{align} Letting $z\mapsto -z$, $$\ln{G(1-z)}=\frac{z}{2}-\frac{z}{2}\ln(2\pi)-\frac{z^2}{2}-\frac{\gamma z^2}{2}-\sum^\infty_{m=2}\frac{\zeta(m)}{m+1}z^{m+1}$$ It follows that \begin{align} \ln{\frac{G(1-z)}{G(1+z)}} =&z-z\ln(2\pi)-2\sum^\infty_{m=1}\frac{\zeta(2m)}{2m+1}z^{2m+1}\\ =&-z\ln(2\pi)+\int^z_0\pi x\cot(\pi x)\ {\rm d}x \end{align} Let $z=\frac{3}{4}$. \begin{align} \ln\left(\frac{G\left(\frac{1}{4}\right)}{G\left(\frac{7}{4}\right)}\right) =&-\frac{3}{4}\ln(2\pi)+2\sum^\infty_{n=1}\int^\frac{3}{4}_0\pi x\sin(2n\pi x)\ {\rm d}x\\ =&-\frac{3}{4}\ln(2\pi)+\frac{1}{2\pi}\sum^\infty_{n=1}\frac{\sin(3n\pi/2)}{n^2}-\frac{3}{4}\sum^\infty_{n=1}\frac{\cos(3n\pi/2)}{n}\\ =&-\frac{3}{4}\ln(2\pi)-\frac{1}{2\pi}\sum^\infty_{n=0}\frac{(-1)^n}{(2n+1)^2}+\frac{3}{8}\sum^\infty_{n=1}\frac{(-1)^{n-1}}{n}\\ =&-\frac{3}{8}\ln{2}-\frac{3}{4}\ln{\pi}-\frac{\mathbf{G}}{2\pi} \end{align} Finally, $$\mathcal{I}=-6\ln{2}-12\ln{\pi}-16\left(-\frac{3}{8}\ln{2}-\frac{3}{4}\ln{\pi}-\frac{\mathbf{G}}{2\pi}\right)=\Large{\frac{8\mathbf{G}}{\pi}}$$

  • 1
    $\begingroup$ Thank you so much for the real method approach. It's ok if it's too complicated, I haven't learned contour integration yet. +1 $\endgroup$ – Venus Nov 12 '14 at 10:27
  • 1
    $\begingroup$ @Venus I am glad you found this answer useful in some way. Thanks. $\endgroup$ – M.N.C.E. Nov 12 '14 at 12:22
  • 1
    $\begingroup$ +1 because you takes care of writing the result at the very end. Usually we have to guess what was the result. Good. $\endgroup$ – Felix Marin Dec 21 '14 at 4:25

Let $f(x) = \tanh(x)\tanh(2x)$. Rewrite the integral at hand as $$I = \int_0^\infty \frac{f(x)}{x^2}dx = \frac12 \int_{-\infty}^{\infty} \frac{f(x)}{x^2} dx = \frac12 \lim_{k\to\infty} \int_{-k\pi}^{k\pi} \frac{f(x)}{x^2} dx\\ $$ For each positive integer $k$, consider the rectangular region $$D_k = \big\{ u + iv \in \mathbb{C} : |u| \le k\pi, 0 \le v \le k\pi \big\}$$ and the contour integral over its boundary:

$$C_k \stackrel{def}{=} \int_{\partial D_k} \frac{f(z)}{z^2} dz = \left( \int_{-k\pi}^{k\pi} + \int_{k\pi}^{k\pi(1+i)} + \int_{k\pi(1+i)}^{k\pi(-1+i)} + \int_{k\pi(-1+i)}^{-k\pi} \right) \frac{f(z)}{z^2} dz $$

$C_k$ split into 4 pieces, one for each edges of the $D_k$. It is not hard to show as $k \to \infty$, the contribution from the three edges (the top, left and bottom) goes to zero. This implies

$$I = \frac12 \lim_{k\to\infty} \int_{\partial D_k} \frac{f(z)}{z^2} dz\tag{*1}$$

Let $\phi = e^{2z}$, we have

$$\begin{align}f(z) &= \tanh(z) \tanh(2z) = \left(\frac{\phi - 1}{\phi+1}\right)\left(\frac{\phi^2-1}{\phi^2+1}\right) = \frac{(\phi-1)^2}{\phi^2+1} = 1 - \frac{2\phi}{\phi^2+1} \\ &= 1 - \frac{1}{\cosh 2z}\end{align}$$

Recall the well known? expansion of $\cot z$

$$\cot z = \sum_{n=-\infty}^\infty \frac{1}{z - n\pi}$$

We have

$$\begin{array}{rrl} & \frac{1}{\sin z} &= \frac{1+\cos z}{\sin z} - \frac{\cos z}{\sin z} = \cot\frac{z}{2} - \cot z = \sum_{n=-\infty}^\infty \frac{(-1)^n}{z - n\pi}\\ \implies & \frac{1}{\cos z} &= -\frac{1}{\sin(z - \frac{\pi}{2})} = \sum_{n=-\infty}^\infty \frac{(-1)^{n-1}}{z - (n+\frac12)\pi}\\ \implies & \frac{1}{\cosh z} &= \frac{1}{\cos(-i z)} = -i \sum_{n=-\infty}^\infty \frac{(-1)^n}{z - (n+\frac12)\pi i}\\ \implies & f(z) & = 1 + \frac{i}{2} \sum_{n=-\infty}^\infty \frac{(-1)^n}{z - (n+\frac12)\frac{\pi}{2} i}\tag{*2} \end{array}$$

Inside $D_k$, $f(z)$ has poles at $(n + \frac12)\frac{\pi}{2} i$ for each $n \in \mathbb{N}$. We can evaluate the contour integral in $(*1)$ by summing the residues at these poles. As a result,

$$I = \frac12 (2\pi i)(\frac{i}{2})\sum_{n=0}^\infty \frac{(-1)^n}{((n+\frac12)\frac{\pi}{2}i)^2} = \frac{8K}{\pi}$$

where $\;\displaystyle K = \sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)^2}\;$ is the Catalan's constant.


If one want to minimize the use of complex analysis, an alternate starting point is the expansion of $f(z)$ in $(*2)$. Let $\alpha_n = (n+\frac12)\frac{\pi}{2}$ and notice $\alpha_{-1-n} = -\alpha_n$, we have

$$f(x) = 1 + \frac{i}{2}\sum_{n=0}^\infty (-1)^n\left(\frac{1}{x -\alpha_n i} - \frac{1}{x + \alpha_n i}\right) = 1 - \sum_{n=0}^\infty \frac{(-1)^n \alpha_n}{x^2 + \alpha_n^2} $$ Since $f(0) = 0$, we have

$$\frac{f(x)}{x^2} = \frac{f(x)-f(0)}{x^2} = \frac{1}{x^2} \sum_{n=0}^\infty (-1)^n \alpha_n\left( \frac{1}{\alpha_n^2} - \frac{1}{x^2 + \alpha_n^2}\right) = \sum_{n=0}^\infty\frac{(-1)^n}{\alpha_n(x^2+\alpha_n^2)} $$ If you look at the terms of this series in units of pair, we find the value of any pair is always non-negative. This means we can integrate this series pair by pair and get:

$$\int_0^\infty \frac{f(x)}{x^2}dx = \sum_{n=0}^\infty \frac{(-1)^n}{\alpha_n}\int_0^\infty \frac{dx}{x^2+\alpha_n^2} = \frac{\pi}{2}\sum_{n=0}^\infty \frac{(-1)^n}{\alpha_n^2} = \frac{8}{\pi}\sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)^2} = \frac{8K}{\pi} $$ The same result we obtained using contour integrals.

  • $\begingroup$ Thank you for your answer. I hope someone here will give me an answer with a real analysis method. +1. :-) $\endgroup$ – Venus Nov 11 '14 at 19:46
  • $\begingroup$ Nice answer. +1 $\endgroup$ – Start wearing purple Nov 11 '14 at 20:59
  • $\begingroup$ There is a typo in the first line: The second integral 'start' at $-\infty$. Otherwise, it is quite fine => +1. $\endgroup$ – Felix Marin Nov 11 '14 at 23:26
  • $\begingroup$ Could this problem be tackled by similar means ? $\endgroup$ – Lucian Nov 12 '14 at 1:51
  • $\begingroup$ @FelixMarin thanks, I fixed that. $\endgroup$ – achille hui Nov 12 '14 at 3:43

Write $$ I=\frac{1}{2}\int^{\infty}_{-\infty}\frac{\tanh(x)\tanh(2x)}{x^2}dx=\int^{\infty}_{-\infty}\frac{f(x)}{\cosh(\pi x)}dx, $$ where $f(x)=\frac{2(-1+\cosh(\pi x))}{\pi^2 x^2}$.


If the function $f(z)$ is analytic in $Im(z)>0$ and continuous at $Im(z)\geq 0$. It also satisfies $$ |f(z)|\leq C (1+|z|)^{N} e^{b |Re(z)|}\textrm{, }0\leq b\leq\pi-\epsilon\textrm{, }\epsilon>0 $$ for all $z$ with $Im(z)\geq 0$ (note: here is $b=\pi$, but $N=-2$), then $$ \int^{\infty}_{-\infty}\frac{f(t)}{\cosh(\pi t)}e^{ita}dt=2\sum^{\infty}_{k=0}(-1)^k f(i(k+1/2))e^{-a(k+1/2)}\textrm{, }a>0. $$ Proof. The function $g(z)=\frac{f(z)}{\cosh(\pi z)}$ is meromorphic in $Im(z)>0$ and has poles at $z_k=i(k+1/2)$ with $$ Res(g;i(k+1/2))=f(i(k+1/2))\frac{(-1)^k}{\pi i} $$ a in the real line and meromorphic at $Im(z)>0$. Hence if $m$ is natural number, $R=m$ and $\gamma_R$ is the upper semicircle of diameter $[-R,R]$, then $$ \frac{1}{2\pi i}\int_{\gamma_R}g(z)dz=\sum^{\infty}_{k=0}\frac{(-1)^k}{\pi i}f(i(k+1/2)) $$ For we have $|\cos(\pi R e^{i \theta})|\geq c e^{\pi |\cos(\theta)|}$ and $$ \left|\int^{\pi}_{0}\frac{f(Re^{i\theta})}{\cosh(\pi R e^{i\theta})}iRe^{i\theta}\right|\leq C \left|\int^{\pi}_{0}(1+R)^{-2}Re^{(b-\pi)R|\cos(\theta)|}d\theta\right|\leq C $$ $$ \leq C \int^{\pi}_{0}(1+R)^{-1}d\theta\rightarrow 0\textrm{, when }R\rightarrow \infty. $$ $$ QED $$

For the case $$ f(x)=\frac{2(-1+\cosh(\pi x))}{\pi^2 x^2} $$
we have $$ I=\frac{\pi}{2}2\sum^{\infty}_{k=0}(-1)^k\frac{8(1+\sin(k\pi))}{\pi^2(2k+1)^2}=\frac{8C}{\pi} $$


$$ I=\int^{\infty}_{0}\frac{\tanh(2x)\tanh(x)}{x^2}dx=\int^{\infty}_{0}\left(1-\frac{1}{\cosh(2x)}\right)\frac{dx}{x^2}=2\int^{\infty}_{0}\left(1-\frac{1}{\cosh(x)}\right)\frac{dx}{x^2}. $$ Set $x=\cosh^{(-1)}(t)$ to get $$ I=2\int^{\infty}_{1}\frac{1-1/t}{\sqrt{t^2-1}}\frac{dt}{\cosh^{(-1)}(t)^2}. $$ From $\frac{d}{dt}\left(\frac{1}{\cosh^{(-1)}(t)}\right)=\frac{1}{\cosh^{(-1)}(t)^2\sqrt{t^2-1}}$, we get $$ I=2\int^{\infty}_{1}\frac{1}{t^2\cosh^{(-1)}(t)}dt. $$ Going backwords we set $t=\cosh(y)$. Hence $$ I=2\int^{\infty}_{0}\frac{\tanh(y)}{y\cosh(y)}dy=\frac{8C}{\pi}\tag 1 $$

(1) is here (relation 41)


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.